The pedagogical limitations of inclusive education - and Pozo-Armentia, Araceli del; Reyero, David; Gil Cantero, Fernando (Educational Philosophy and Theory, 2020)
The aim of this article is to contribute to a better conceptual and practical delimitation of inclusive education. A pedagogy that reacts to the need to face the dilemmas of difference. An interpretive and critical methodology with a documentary basis and a normative-pedagogical perspective is used. The results show a tension between theoretical approaches and the practical achievements of inclusive education. The article concludes by considering the position that if the most basic definition of education is essentially inherently inclusive, as it aims to foster the maximum development of everyone, then for the same reason it must also essentially be differentiating. This is precisely because the limits of inclusive education are in recognising and promoting excellence in difference, while the limits of differentiated education lie in recognising and promoting inclusion.
Keywords: Inclusive education; education for all; educational discrimination; equal education